Factors Influencing Intention Resistance to Change: A Study of Jabatan Zakat Negeri Kedah Darulaman - Mohd Fitri, Mansor (2010)
This study investigates the factors influencing intention resistance to change: A study of Jabatan Zakat Negeri Kedah Darul Aman (JZNK). A research model was developed based on Theory of Reasoned Action to indicate the relationship between attitudes and subjective norms towards intention resistance to change. The objectives of the study are to determine the relationship between attitudes towards intention resistance to change and to examine the relationship between subjective norms and intention resistance to change in organization. This study used the quantitative method involving 80 employees of JZNK. The study hypotheses have been tested by using multiple regression analysis. The results of the study found attitudes factor is supported while subjective norms factor is not supported the hypotheses, which accept the hypothesis HI and reject Hz.